1989
DOI: 10.1002/aja.1001860306
|View full text |Cite
|
Sign up to set email alerts
|

Development of arteriovenous anastomoses in the skin of the chicken and the influence of environmental temperature

Abstract: Posthatching differentiation of arteriovenous anastomoses (AVAs) and the effect of heat exposure (38 degrees C) and cold acclimation (2-3 degrees C) on AVA density were studied in naked skin areas (eyelids, comb, wattles) of chickens. The AVAs were identifiable in the newly hatched chick, but they were extremely simple. The number of cell layers in the wall of the AVAs increased from two at hatching to four to five in the 5-month-old chickens. The density of the AVAs increased significantly during posthatching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…26) and could reflect changes in physiology facilitating evaporative and sensible cooling seen in several bird species (e.g. [41][42][43]. Effects of prior experience of warmth on metabolic responses to heat were also comparable to those of relatively large changes in body mass and tarsus length (+1 SD; Fig.…”
Section: Body Size and Tarsus Length Weakly Influence Thermoregulatio...mentioning
confidence: 66%
“…26) and could reflect changes in physiology facilitating evaporative and sensible cooling seen in several bird species (e.g. [41][42][43]. Effects of prior experience of warmth on metabolic responses to heat were also comparable to those of relatively large changes in body mass and tarsus length (+1 SD; Fig.…”
Section: Body Size and Tarsus Length Weakly Influence Thermoregulatio...mentioning
confidence: 66%
“…Additionally, the countercurrent heat exchange and arteriovenous anastomoses (AVAs) systems enable avian species to have their feet in contacting with cold surface at high endogenous heat production and energy costs (Hillman et al, 1982;Midtgard, 1989). In the current study, compared to NP hens, both WP and AP hens were able to maintain their core temperature, but the underlaying mechanisms could be different.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it has also been stated that metabolic factors should be taken into consideration to maintain AVA density (Morris, 1984). It has been reported that the density of AVA in chics increases noticeably during the posthatching period and that the number of cell layers in the AVA wall amounts to 4-5 in chicken of 5 months, whereas it is 2 in the newly-hatching chics (Midtgard, 1989). In the studies carried out until now, the time of the increase in AVA density cannot completely be determined and, in addition, the increase in the activity should also be considered (Clark, 1938;Midtgfird, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the AVA development relating to human nasal mucosa (Rosatti, 1954) and human ear (Prichard, 1956) was studied. This development was also studied in the ears of rabbits (Clark, 1934b;Morris, 1984;1986), the skins of chicken (MidtgArd, 1989) and the tongues of kittens (Jasinsky, 1979). However, no AVAs were noted in rabbits under 8 day (Morris, 1984) and in 4-day kittens (Jasinsky, 1979).…”
mentioning
confidence: 99%